Pengaruh Quality Product dan Brand Trust terhadap Customer Loyalty melalui Customer Satisfaction Fore Coffee di Kota Semarang - Dina Lestiana; Ibnu Khajar (Lembaga Yasin AlSys, 2026)
Increasing competition in Indonesia’s coffee industry requires companies to understand the factors that shape customer loyalty sustainably. However, previous research findings regarding the influence of product quality and brand trust on customer loyalty, as well as the role of customer satisfaction as a mediating variable, remain inconsistent. This study aimed to analyze the influence of product quality and brand trust on customer loyalty through customer satisfaction among Fore Coffee consumers in Semarang City. This study used an explanatory quantitative approach involving 243 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using the Partial Least Square (PLS) method with the assistance of SmartPLS. The results showed that product quality and brand trust had a positive and significant effect on customer satisfaction and customer loyalty. In addition, customer satisfaction was proven to partially mediate the relationship between product quality and brand trust and customer loyalty. The conclusion of this study confirms that improving product quality and brand trust can consistently shape customer loyalty through customer satisfaction. The implications of this study emphasize the importance of corporate strategies in maintaining product quality and building brand trust to improve customer satisfaction and customer loyalty sustainably.